A Carbohydrate–Anion Recognition System in Aprotic Solvents. Issue 5 (11th March 2014) - Ren, Bo; Dong, Hai; Ramström, Olof
Abstract A carbohydrate–anion recognition system in nonpolar solvents is reported, in which complexes form at the B‐faces of β‐D‐pyranosides with H1‐, H3‐, and H5‐cis patterns similar to carbohydrate–π interactions. The complexation effect was evaluated for a range of carbohydrate structures; it resulted in either 1:1 carbohydrate–anion complexes, or 1:2 complex formation depending on the protection pattern of the carbohydrate. The interaction was also evaluated with different anions and solvents. In both cases it resulted in significant binding differences. The results indicate that complexation originates from van der Waals interactions or weak CH⋅⋅⋅A− hydrogen bonds between the binding partners and is related to electron‐withdrawing groups of the carbohydrates as well as increased hydrogen‐bond‐accepting capability of the anions.